Structural characterization and immunomodulatory effect of a polysaccharide HCP-2 from Houttuynia cordata - Cheng, Bao-Hui; Chan, Judy Yuet-Wa; Chan, Ben Chung-Lap; Lin, Huang-Quan; Han, Xiao-Qiang; Zhou, Xuelin; Wan, David Chi-Cheong; Wang, Yi-Fen; Leung, Ping-Chung; Fung, Kwok-Pui; Lau, Clara Bik-San (Carbohydrate polymers, 2014)
•A pure pectic polysaccharide (named HCP-2) was obtained from the water extract of Houttuynia cordata.•HCP-2 was chemically characterized using acid hydrolysis, PMP derivation, FTIR and NMR.•HCP-2 exhibited immunomodulatory effects in vitro. Immunomodulation of natural polysaccharides has been the hot topic of research in recent years. In order to explore the immunomodulatory effect of Houttuynia cordata Thunb., the water extract was studied and a polysaccharide HCP-2 with molecular weight of 60,000Da was isolated by chromatography using DEAE Sepharose CL-6B and Sephacryl S-400 HR columns. The structure characterization of HCP-2 was performed by Fourier transform infrared spectroscopy (FTIR), acidic hydrolysis, PMP derivation, HPLC analysis and nuclear magnetic resonance spectra (NMR). HCP-2 was elucidated as a pectic polysaccharide with a linear chain of 1,4-linked α-d-galacturonic acid residues in which part of the 6-carboxyl groups were methyl esterified and part of 2-hydroxyl groups were acetylated. The bioactivity assays showed that HCP-2 could increase the secretions of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), macrophage inhibitory protein-1α (MIP-1α), macrophage inhibitory protein-1β (MIP-1β), and RANTES (regulated on activation, normal T cell expressed and secreted) in human peripheral blood mononuclear cells (PBMCs), which play critical roles in the innate immune system and shape the adaptive immunity. Our results implied that HCP-2 could be an immune enhancer.